The Keyes Mica Mines - Thompson, Woodrow B; Falster, Alexander U; Mortimer, Thomas J (Rocks & minerals, 2022)
Several localities in the pegmatite field particularly the Palermo and Fletcher mines contain rich phosphate assemblages that have supplied countless specimens for collectors and mineralogical research. Paul Moore's classic paper on pegmatite phosphates (Moore 1973) inspired mineral collectors and scholars with fresh insights into the subject and helped them to identify specimens from the Palermo mines and other nearby localities. In this article the authors describe the history, geology, and minerals of the Keyes mica mines in the Grafton County town of Orange. These mines are located 7.4 kilometers southwest of the famous Palermo No. 1 mine. They include two principal pits and four smaller pits. The No. 1 mine produced many attractive minerals during the final years of mining in the mid-1900s. The Keyes specimens most seen in collections are blue-green, green, purple, and bicolored fluorapatite crystals; groups of freestanding muscovite crystals; and fine albite crystals. Others include aquamarine and golden beryl crystals, quartz crystals, and numerous primary and secondary phosphates. One of us (WBT) visited the Keyes mines several times starting in 1961 when they were still active. These trips inspired a long-term interest in the locality, resulting in an examination of many Keyes specimens in private and institutional collections. There are few published references to Keyes minerals. One, Philip Morrill's (1960) New Hampshire collecting guidebook lists species known or alleged to have been found at the mines.